2017
DOI: 10.1093/dote/dox149
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on esophagectomy: a meta-analysis

Abstract: The impact of body mass index (BMI) on postoperative outcomes after curative resection for esophageal cancer has been assessed in many studies worldwide with conflicting conclusions. The aim of this meta-analysis is to evaluate the influence of preoperative BMI on surgical and oncologic outcomes after radical surgery for esophageal cancer, in Western studies. A comprehensive electronic search was performed to identify Western publications reporting BMI and outcomes following surgery for esophageal cancer. Arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 32 publications
5
29
3
1
Order By: Relevance
“…The association between a BMI of ≥26 kg/m 2 and higher incidence of anastomotic leakage was also found in other studies and could be explained by a higher rate of intra‐operative complications such as accidental injury and ischaemia …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The association between a BMI of ≥26 kg/m 2 and higher incidence of anastomotic leakage was also found in other studies and could be explained by a higher rate of intra‐operative complications such as accidental injury and ischaemia …”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, two reviews showed that patients with a high BMI have a better overall 5 years of survival, which was not encountered in the present study . This phenomenon is also seen in other types of cancer and is called the BMI paradox.…”
Section: Discussionsupporting
confidence: 41%
“…While overall postoperative morbidity rates appear to be similar among patients with obesity compared with normal weight and underweight individuals, specific complications may be increased among patients with obesity. A recent meta-analysis reported a markedly increased risk of anastomotic leak, up to 35%, among patients with BMI-defined obesity, but otherwise similar postoperative outcomes (26). A clear technical difficulty may be the preparation of an optimal gastric conduit, without tension.…”
Section: Surgerymentioning
confidence: 99%
“…Notwithstanding a clear epidemiologic association, the impact of VO and MetS on oncologic outcomes of EAC remains uncertain, with various data suggesting improved, worsened or an unchanged survival and treatment outcomes (24)(25)(26)(27). With respect to esophageal cancer surgery, although VO may impact operative outcomes through increased technical difficulty, and associated comorbidities may increase perioperative risk, the current literature are highly inconsistent in this regard (26), possibly due to the differential impact of various stages of obesity and comorbidity on perioperative risk, and the confounding effect of malnutrition and loss of lean body mass, known as sarcopenia, which is present in many patients with esophageal cancer (28,29). Across oncology a greater understanding of obesity and tumor biology is sought, and a 2014 statement from the American Society of Clinical Oncology (ASCO) commits to addressing this issue through increased education, and the delivery resources for healthcare professionals to tackle obesity in partnership with patients, in addition to increasing provisions for public health policy supporting the prevention and treatment of obesity (30).…”
Section: Introductionmentioning
confidence: 99%
“…This study was followed by several reports from Asian countries confirming these results for oesophageal and gastric adenocarcinoma, and GC, but reporting discordant results for oesophageal SCC …”
Section: Discussionmentioning
confidence: 53%